Cross-field optoelectronic modulation via inter-coupled ferroelectricity in 2D In2Se3 - Debopriya Dutta (Nature Portfolio, 2021)
Abstract The ability to couple the in-plane (IP) and out-of-plane (OOP) dipole polarizations in ferroelectric In2Se3 makes it a promising material for multimodal memory and optoelectronic applications. Herein, we experimentally demonstrate the cross-field optoelectronic modulation in In2Se3 based field-effect devices. Surface potential measurements of In2Se3 based devices directly reveal the bidirectional dipole locking following high gate voltage pulses. The experimental evidence of hysteretic change in the IP electrical field facilitating a nonvolatile memory switch, was further explored by performing photocurrent measurements. Fabricated photodetectors presented multilevel photocurrent characteristics showing promise for nonvolatile memory and electro-optical applications.